Phases of psychological response in COVID-19: A preliminary heuristic - Everly Jr, PhD, George S.; Wu, MD, MPH, Albert W.; Potash, MD, MPH, James B. (American Journal of Disaster Medicine, 2021)
Objective: To explore the putative phases of the psychological response to disaster: preimpact, impact, heroic, honeymoon, disillusionment, and recovery, and make recommendations for corresponding interventions. Conclusions: Disasters such as the COVID-19 pandemic are often characterized by chaos and uncertainty. As a result, public health disaster planning and response represent formidable challenges. Although disasters can result from a wide array of hazards, regardless of the agent at work, they may follow a rather predictable trajectory of psychological phases. A heuristic of those phases can provide an opportunity for a more organized disaster mental health response and more efficient utilization of scarce resources.